(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
The paper aims to present Lower Triassic lithofacies definition and first conodont fauna of Gorski Kotar region, Croatia. The depositional environment is envisaged as shallow marine realm of a passive continental margin. Sedimentary complex differentiates in predominantly carbonate sedimentation that characterises the beginning of deposition with upward increasing trend of terrigeneous influx. Lithofacial units have been defined as oolitic bar facies, lagoonal facies, shoreface-offshore facies, ooid-sandy shoal facies, restricted bay facies and flat-pebble conglomerate facies. The following conodont taxa were collected: Ellisonia sp., Foliella gardenae, Hadrodontina sp., Hindeodus parvus, Hindeodus sp., Pachycladina obliqua, ?Parachirognathus sp., Platyvillosus costatus and Pl. hamadai. The oldest strata yield Hindeodus parvus marking lowermost Triassic. The biostratigraphical data enable recognition of the parvus-isarcicella zones, obliqua Zone and Platyvillosus Subzone. The finds of Hindeodus parvus, Platyvillosus costatus and Pl. hamadai represent their first records in the External Dinarides and enable correlation of the Early Triassic conodont faunas of the Western Tethyan realm.